The BENAR RELAXATION THERAPY (BRT) DECREASING PSYCHOLOGIC SYMPTOMS IN DIABETES TYPE II IN CANDIBINANGUN DISTRIC - Hidayati, Rizqi Wahyu; Rukmi, Dwi Kartika (Jurnal Keperawatan Respati Yogyakarta, 2021)
Diabetes prevalence in Yogyakarta is the second highest in Indonesia, and Diabetes sufferers are prone to experiencing physical and psychological disorders. Psychological disorders such as depression, stress, and anxiety are more at risk in Diabetes patients. This condition will be worsen the prognosis and outcome, so managing psychological disorders in Diabetes patients is essential. One of the efforts to manage mental disorders in Diabetes patients is non-pharmacological therapy such as Benar Relaxation Therapy (BRT). It combining between aromatherapy and Benson relaxation techniques which is effective for mild and moderate anxiety therapy. In this study, the BRT try to test the effectivity stress, anxiety, until depression. This therapy using three sickles of therapy and the dose of the aromatherapy was three drops in 20 ml of sterile water which formulated by the researcher. The aim study is evaluate the effect of Benar Relaxation Therapy (BRT) in reducing psychological symptoms in diabetes patients. This study did Quasi-experimental research with a pre-posttest without control group design. 14 adults Diabetes patients who ADL independently and have cellphones with video features in Candibinangun district purposively taken to this study. For three consecutive days, patients received therapy for 15 minutes. Their psychological symptoms were measured using the DASS 21 and PSQI questionnaires. Meanwhile, the measurement of physiological symptoms is to measure blood pressure, pulse, and blood glucose. The data processed using the T-test and Wilcoxon test according to the results of data normality. The results showed that Benar Relaxation Therapy effectively reduced psychological symptoms in the form of depression (p = 0.038) and improved sleep quality (p = 0.042). Physiologically, this therapy was also effective in lowering blood pressure (p = 0.00). However, this therapy is not significant in reducing psychological and physiological symptoms in stress, anxiety, pulse, and blood glucose levels. The conclusions is the Benar Relaxation Therapy in this study was effective in lowering depression scores and blood pressure. This therapy also improves the quality of sleep in type 2 Diabetes patients. However, this therapy significantly increases the patient's stress and anxiety and has no significant effect on pulse and blood glucose levels. Keywords: Benar Relaxation Therapy; Psychologic Symptoms